EL MUNDO IMPRESO SE CONSOLIDA. Análisis de los periódicos costarricenses (1851-1870) - Vega, Patricia (1995)
The present article analyses the evolution of costarrican press from 1851 to 1870. It has the objetive to study tbe causes that convery to an increase of its ptoduction and distribution areas, its price and approach to writters and editors of prints.